Cosmologia de partículas no universo primordial: repovoamento pós-inflacionário via preheating e reheating - Monteiro, Letícia Cavalcante (2019)
This work focuses on the study of the early stages of the universe, in particular the inflationary era and the post-inflationary period, which includes preheating and reheating.Such topics are of great importance in understanding the evolution of the universe and its present structure, since inflation is the source of the initial perturbations that originated the structures at large scales that we observe today, and it explains the fact that the universe is practically homogeneous, isotropic and flat (horizon and flatness problems). Inflation was originally proposed by Alan Guth in the early 1980s and consists of an era of exponential expansion driven by a scalar field called the inflaton. As this epoch occurs at very high energies, understanding the dynamics of this expansion allows us to establish certain parameters that restrict in inflationary models. After this period, we need to repopulate the universe. The oscillations of the inflaton field cause this particle to decay into other degrees of freedom, that is, other particles, leading to the evolution of standard cosmology with the universe being dominated by radiation at that time. There are two main mechanisms for this type of decay: preheating (broad parametric resonance regime) and reaheating (usual decay regime). Depending on the model, one of the mechanism may be dominant over the other, or even none of them could be relevant.